Peran Majelis Kehormatan Disiplin Kedokteran Indonesia Dalam Kasus Pelanggaran Standar Profesional Dokter - Indrawan, Khadafi; Fakih, M.; Budiyono, Budiyono (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
In Indonesia, the increase in the number of medical disputes reflects dissatisfaction with health services. This study aims to analyze the role of MKDKI as a law enforcement tool in cases of violation of doctors' professional standards, as well as supporting and inhibiting factors for the implementation of this role. The research method used is the empirical normative method. The data collected was analyzed to identify how MKDKI carried out its role in handling violation cases. The results of the study show that the Government has established laws and established KKI, MKDKI, and MKEK to protect the doctor-patient relationship. This panel assesses disciplinary violations based on operational and professional standards. The effectiveness of the Assembly is influenced by regulations, member commitment, institutional support, and resources. Obstacles such as inadequate regulation and external intervention need to be overcome through regulatory revision strategies, increased resources, and transparency. The suggestion in this study is to increase transparency and consistency in handling cases of violations of doctors' professional standards, the Indonesia Medical Honorary Council (MKDKI) needs to be supported by strong regulations and the support of related institutions. It is also important to establish MKDKI in each province and conduct socialization about their roles, as well as ensure that their decisions are in line with the Indonesia Medical Council (KKI)